Evaluation of the perception of the importance of gums in smile aesthetics by laypeople and Dentistry students (Research, Society and Development, 2023)
The smile has a great impact on facial aesthetics. As it is a subjective and mutable concept, there is no single type of smile that is considered an absolute beauty standard. The balanced exposure of soft and hard tissue during the smile also has a significant impact on the overall aesthetic perception. The objective of this study was to evaluate the perception of the impact of the gums on smile aesthetics by dentistry students and laypeople. We conducted a descriptive-transversal study, where data was obtained through a questionnaire with photographs and subsequently interpreted according to the frequency of responses. A total of 220 people were evaluated, 147 (66.8%) women and 73 (33.2%) men, of whom 35.4% had an academic background in dentistry. We observed a constant similarity between the groups, showing that laypeople, even without broad knowledge compared to dentistry students, were able to identify important characteristics in a gummy smile. The perception of the importance of the gums in smile aesthetics is subjective to each individual and is generally related to beauty and harmony. We concluded that the population is critical in evaluating smile components. Among the academics, caution and prudence were observed in the aesthetic evaluation of the smile. Among the different levels of gum exposure, Image 2 with a medium smile of 3 to 4mm received the highest scores.